Antioxidant Property and Inhibition of Tyrosinase and Melanin Synthesis of the Korean Fir (Abies koreana Wilson) Needle Extracts: Antioxidant and skin-whitening activities of Abies koreana - Min Young Kim; Ji Hye Kim (Journal of Tropical Life Science, 2023)
Korean fir (Abies koreana Wilson) is traditionally used in folk medicine for its antibacterial, memory-enhancing, and anti-inflammatory properties. In this study, we evaluated the antioxidant and skin-whitening effects of the methanol and ethanol extracts of Korean fir needles. The extracts were tested for their antioxidant capacity using various assays, including radical scavenging (1,1-diphenyl-2-picrylhydrazyl, O2-, H2O2 and NOÂž), SOD-like, ferrous ion chelating, and reducing power assays. The total phenolic and flavonoid contents were determined by the Folin-Ciocalteu method. The non-toxic doses of the extracts were determined by MTT assay using human malignant melanoma SK mel-100 cells, and the tyrosinase activity and melanin contents were measured using an enzyme-substrate assay. The results showed that the antioxidant activity of the Korean fir needle extracts increased in a dose-dependent manner, as confirmed by their radical scavenging activities in the 2,2-diphenyl-1-1-picrylhydrazyl and 2,2-azino-bis-(3-ethylbenzthiazoline-6-sulfonic acid) assays. The Korean fir needle extract significantly reduced tyrosinase activity and melanin content in a dose-dependent manner (p < 0.01), suggesting its potential use as a skin-whitening agent. The methanol extracts of the Korean fir needles exhibited significantly higher phenolic (8306 mg gallic acid equivalents/100 g) content, with higher superoxide (IC50 = 4.22 mg/mL) and nitric oxide (IC50 = 1.50 mg/mL) radical scavenging activities and inhibition of tyrosinase and melanin synthesis than those of ethanol extracts (p < 0.05). Overall, our results demonstrate the potential of Korean fir (Abies koreana Wilson) needles as a source of tyrosinase inhibitors and antioxidants for inhibiting melanin biosynthesis, which could have applications in the cosmetic and pharmaceutical industries.